NTA UGC NET/SET/JRF - Paper 1: teaching and research aptitude - Madaan, K. V. S. (Noida: Pearson India Education, 2024)
This book, in its third edition, is designed and developed for students who aspire to build a career in academics and research field. It also prepares the candidates to qualify the National Eligibility Test (NET) and develop teaching and research aptitude in real terms. Divided into ten units, this edition includes all important topics of Teaching and Research aptitude and applications as per the latest syllabus (NET Paper I). A perfect blend of theory, practice questions, and discussions in the chapters are supported by updated facts, figures, diagrams and tables. This title specifically helps students to assess their reasoning ability, comprehension, divergent thinking and general awareness. https://www.pearsoned.co.in/web/books/9789353433741_UGC-NETSET-paper-1--English_KVS-Madaan.aspx
able of contents: Preface About NTA About the Author Syllabus Strategy about NTA-UGC NET Exam 1 Teaching Aptitude 2 Research Aptitude 3 Reading Comprehension 4 Communication 5 Mathematical Reasoning and Aptitude 6 Logical Reasoning 7 Data Analysis and Interpretation 8 Information and Communication Technology 9 People, Development and Environment 10 Higher Education System: Governance, Polity, and Administration UGC NET Paper 1 December 2012 UGC NET Paper 1 June 2013 UGC NET Paper 1 Reconduct June 2013 (in September, 2013) UGC NET Paper 1 December 2013 UGC NET Paper 1 June 2014 CBSE-UGC NET Paper 1 December 2014 CBSE-UGC NET Paper 1 June 2015 CBSE-UGC NET Paper 1 December 2015 CBSE-UGC NET Paper 1 July 2016 CBSE-UGC NET Paper 1 January 2017 CBSE-UGC NET Paper 1 November 2017 CBSE-UGC NET Paper 1 July 2018 CBSE-UGC NET Paper 1 December 2018 CBSE-UGC NET Paper 2 December 2018
Keywords: UGC - NET; NTA - NET; Teaching and research aptitude; Paper I